Teoria e prática sobre planejamento e orçamento plurianuais - Constantino Cronemberger Mendes; Welles Matias de Abreu; Thiago Silva e Souza (Instituto de Pesquisa Econômica Aplicada (IPEA), 2021)
– This study deals with state action through the analysis of the main administrative instruments with planning and budgeting, aiming to illustrate the different characteristics between the planning and budgeting instruments under the multi-annual perspective and to present possible risks of becoming a substitute and multi-annual devices, not complimentary, within the political process of public decision. The budget is a political-political instrument with an allocation structure of public resources and expenditure on entities considered to be of public interest. Planning, in turn, is closely linked to the State's distributive function, to the problems of identifying social demand, public choice, and prioritizing public goods. Both the allocative function of the budget and the distributive function exercised using planning are integrated or interrelated but are limited to the fi scal and fi nancial conditions of the State for maintaining macroeconomic balance. Among the four constitutional amendments pending in the National Congress on planning and budget, only one brings an interpretation of the multi-annual budget as a substitute for the Multi-Annual Plan (PPA), under the national medium-term scope of the federal government. In this context, the possibility of removing the constitutional requirement of the PPA to be a law without a clear proposal to replace it does not fail to create an institutional instability about the fate of planning and budgeting in Brazil. In this sense, this work brings subsidies to stimulate the necessary debate with society regarding the project that is on the legislative table to, for the time being, extinguish the PPA to implement and a multi-annual budget.
Keywords: H; H1; H11; H5; H53; H6; H61; 330; planning; budget; multiannual; public choice; federal constitution